2017
DOI: 10.18203/2394-6040.ijcmph20174826
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and attitude of medical and nursing students towards screening for cervical carcinoma and HPV vaccination in a tertiary care teaching hospital

Abstract: Background: Cervical cancer is the second most common cancer among women and infection with high risk human papilloma virus (HPV) is a pre-requisite for cervical cancer. The present study was undertaken to assess the knowledge regarding cervical cancer screening and HPV vaccination among medical and nursing staff.Methods: Four hundred participants; 200 MBBS students, 120 BSc nursing students and 80 staff nurses answered a standardized questionnaire which was analysed.Results: Majority of the MBBS students corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
(25 reference statements)
2
13
1
1
Order By: Relevance
“…A recent study conducted among medical and nursing students regarding knowledge and attitude of HPV vaccination in tertiary care teaching hospital by Ganju SA et al, concluded that there was enough knowledge regarding HPV vaccination but there were several gaps regarding its safety, efficacy and availability. 13 Medical teaching has definitive impact in the awareness regarding HPV vaccination and prevention of cervical cancer. Students of only one institution were included in the study which is the major limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted among medical and nursing students regarding knowledge and attitude of HPV vaccination in tertiary care teaching hospital by Ganju SA et al, concluded that there was enough knowledge regarding HPV vaccination but there were several gaps regarding its safety, efficacy and availability. 13 Medical teaching has definitive impact in the awareness regarding HPV vaccination and prevention of cervical cancer. Students of only one institution were included in the study which is the major limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge and attitude of the effect of human papilloma virus and its preventive measures is very important in preventing the cervical cancer .Early screening prevents upto 80% of the invasive cancer cases .But lack of education and cultural patterns have been known as major reasons for low screening prevalence in many developing countries [7] . Awareness plays a major role in improvising the preventive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Inspite of proven efficacy of HPV Vaccine, the vaccination is very poor in india this is mainly due to lack of adequate knowledge and non availability of vaccine are the major factors for poor acceptance of vaccination [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 HPV'nin serviks kanseri oluşumunda kesin nedenlerden biri olduğu açıkça ortaya konulmuştur ve dünya çapında en yaygın cinsel yolla bulaşan virüslerden biridir. 6,7 Uzun vadede HPV hem benign hem de malign anogenital hastalıklara ve ayrıca baş-boyun lezyonlarına neden olmaktadır. 8 Erkekler genellikle asemptomatik olsa da HPV enfeksiyonu hem erkekleri hem de kadınları etkilemektedir.…”
unclassified